2010
DOI: 10.1002/chem.201000627
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Methane to Methanol: Nickel, Palladium, and Platinum (d9) Cations as Catalysts for the Oxidation of Methane by Ozone at Room Temperature

Abstract: The room-temperature chemical kinetics has been measured for the catalytic activity of Group 10 atomic cations in the oxidation of methane to methanol by ozone. Ni(+) is observed to be the most efficient catalyst. The complete catalytic cycle with Ni(+) is interpreted with a computed potential energy landscape and, in principle, has an infinite turnover number for the oxidation of methane, without poisoning side reactions. The somewhat lower catalytic activity of Pd(+) is reported for the first time and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 58 publications
5
44
0
Order By: Relevance
“…The genuine gas‐phase catalytic oxidation CH 4 →CH 3 OH by MO + was realized quite some time ago for FeO + 34a and, more recently, for NiO + and PdO + 67. On the basis of computational and experimental studies, it was shown that NiO + , owing to its easy availability and high selectivity, is a rather promising candidate, and experiments that use NiO‐ or FeO‐doped zeolites as catalyst for the oxygenation of CH 4 under ambient conditions are also encouraged by computational and (for iron and copper) experimental investigations 68…”
Section: The Conversion Of Methane To Methanol: a Long‐time Conundmentioning
confidence: 99%
“…The genuine gas‐phase catalytic oxidation CH 4 →CH 3 OH by MO + was realized quite some time ago for FeO + 34a and, more recently, for NiO + and PdO + 67. On the basis of computational and experimental studies, it was shown that NiO + , owing to its easy availability and high selectivity, is a rather promising candidate, and experiments that use NiO‐ or FeO‐doped zeolites as catalyst for the oxygenation of CH 4 under ambient conditions are also encouraged by computational and (for iron and copper) experimental investigations 68…”
Section: The Conversion Of Methane To Methanol: a Long‐time Conundmentioning
confidence: 99%
“…2d, 4, 12, 20 For example, MO . + can be generated through the oxidation of M + by, for example, O 3 ,21 N 2 O,22, 23 and other terminal oxygen sources, and Fourier transform ion‐cyclotron resonance (FTICR) mass spectrometry has often been employed to perform the IMRs 24. To achieve an efficient conversion of M + to MO .…”
Section: Resultsmentioning
confidence: 99%
“…1930-1980, a golden age for ionic studies in vacuum. The selection of major subjects omits important topics such as development of ion/ion collisions, 27) the demonstration of catalytic reaction in the gas phase, 28) and the measurement of collision cross sections 29) and many others.…”
Section: Ion Chemistrymentioning
confidence: 99%